The Positive Impact of the Problem Based Learning Model Assisted by Audio Visual Media on the Science Knowledge Competency - Astuti, Ni Kadek Sri; Agustika, Gusti Ngurah Sastra; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2024)
The number of students who need to improve in understanding science learning material is caused by using less than optimal learning components. This study aimed to analyze the effect of the problem-based learning model assisted by audio-visual media on the competence of science knowledge in fifth-grade elementary school. This research is a quasi-experimental study with a non-equivalent control group design. The population in this study was fifth-grade students. The sample in this study was determined by cluster random sampling technique. The sample in this study was fifth-grade elementary school students. Data in this study were collected using the multiple-choice test method. The collected data were then analyzed using descriptive and t-test inferential statistical analysis techniques. The results of the t-test analysis obtained count = 8.413 and table = 4.027 with a significance level of 5%. These calculations show that tcount>ttable, so H0 is rejected, and H1 is accepted. Therefore, the problem-based learning model assisted by audio-visual media significantly influences the science knowledge competence of fifth-grade elementary school students. The implication of this research is to improve students' science knowledge competence.